2016
DOI: 10.1016/j.ijid.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection may increase the risk of progression of chronic hepatitis B disease among the Chinese population: a meta-analysis

Abstract: These results indicate a strong relationship between H. pylori and chronic hepatitis B, particularly during HBV progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 24 publications
1
29
1
Order By: Relevance
“…Several studies detected a similar high association between the frequency of H. pylori infection and liver cirrhosis. [27][28][29] A Chinese study found a higher prevalence (72%) of H. pylori in Chinese HBV patients than in the control group (39%). 30 However, in the present study, strong association could not be detected between the prognosis of the liver condition and H. pylori infection, except in the level of ALP.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies detected a similar high association between the frequency of H. pylori infection and liver cirrhosis. [27][28][29] A Chinese study found a higher prevalence (72%) of H. pylori in Chinese HBV patients than in the control group (39%). 30 However, in the present study, strong association could not be detected between the prognosis of the liver condition and H. pylori infection, except in the level of ALP.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of H. pylori infection among patients with chronic hepatitis B is around 30-80% [17]. H. pylori infection is confirmed in 79% of patients with postinflammatory liver cirrhosis connected with HBV infection [18].…”
Section: Chronic Hbv and Hcv Infectionsmentioning
confidence: 99%
“…Frequency of H. pylori infection among patients with chronic hepatitis B correlates with the incidence of hepatocellular cancer, both in men and women [20]. Among this type of patients, fast progression of inflammatory changes in the liver is observed, as well as intensified fibrosis, which promotes occurrence of primary neoplastic lesions [17,21].…”
Section: Chronic Hbv and Hcv Infectionsmentioning
confidence: 99%
See 2 more Smart Citations